Pengaruh Gaya Belajar Kinestetik terhadap Kemampuan Roll Depan pada Siswa SMP - Andi Ihsan (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to analyze the influence of kinesthetic learning styles on the forward roll ability of students at SMP Negeri 1 Tinggi Moncong Malino, Gowa Regency, South Sulawesi. The kinesthetic learning style was chosen because it emphasizes active student involvement through direct experience and movement practice, which is believed to improve motor coordination, motor memory, and self-confidence in physical activity. This study used a quantitative descriptive method with a pre-test and post-test design. The sample consisted of eight eighth-grade students with a predisposition for kinesthetic learning styles. Data were collected through a floor exercise practice test that assessed three main aspects: the preparation stage, movement execution, and final stance. Data analysis used a paired t-test to determine differences in results before and after the implementation of the kinesthetic method. The results showed a significant improvement in students' forward roll ability. The average pre-test score of 7.13 increased to 10.25 in the post-test, with an average difference of 3.125 points. The calculated t-value of -5.693 is greater than the t-table of -2.365 with a significance level of p = 0.001 < 0.05, indicating a significant difference. Thus, kinesthetic learning style-based learning has been proven effective in improving students' motor skills, motor coordination, and self-confidence. Therefore, physical education teachers are advised to consistently integrate this method in learning basic motor skills, especially floor gymnastics.